An Intelligent Control and Switching for the Optimization of Street Lighting - Tan, Jian-Ding; Tiong, Sieh-Kiong; Koh, Siaw-Paw; Hen Chong, Kok; Koay, Ying-Ying (International Journal of Engineering and Technology, 2018)
The objective of this research is to propose an Artificial Intelligent method to optimize the performance of street lightings. The method proposed in this research is by using the Electromagnetism-Like Mechanism (EM) global optimization algorithm. The proposed EM is designed to minimize the power consumption and maximize the life span of the lamps by different switching configurations and by adjusting the intensities of the lights. Simulation results indicate that the proposed algorithm can significantly reduce the power consumption of the system and drastically increase the projected life span of the lamps used. The main power savings can be found in the early stages of the graph. This shows that the evening sun rays and twilight help illuminate the street, rendering full intensity of street lights a waste. This, in turn, significantly prolonged the lifespan of the lamps used in the street lightings. It can thus be concluded that the proposed algorithm gives significantly positive impact in optimizing the performance of a street lighting system. The search speed and accuracies of the EM can be further improved by modifying or incorporating other search mechanism into the EM in future extension of the research.Â Â